An integrated product conceptual scheme decision approach based on Shapley value method and fuzzy logic for economic-technical objectives trade-off under uncertainty. (June 2021) - Jing, Liting; Zhan, Yunfei; Li, Qizhi; Peng, Xiang; Li, Jiquan; Gao, Fei; Jiang, Shaofei
Highlights: The SHVM is able to describe the trade-off law of economic-technical objectives. The evidence trust function using fuzzy logic to integrate group evaluation data. No weight auxiliary information in the uncertainty decision process. The prototype system (CSTD) is developed to support multi-objective decision. Abstract: Conceptual design decisions form part of a multi-objective evaluation process that plays a critical role in product development. However, when there is interaction among the evaluation objectives, existing decision methods are difficult to determine the influence degree of each objective on the overall design desirability, which can lead to an unreliable decision regarding the most optimal scheme. In addition, it is difficult to deal with the vague judgments for qualitative objectives in decision-making under subjective decision environment. To maximize the overall design desirability of the scheme, An integrated product conceptual scheme decision approach based on Shapley value method and fuzzy logic model is proposed to transform the multi-objective conflict into a game problem of multi-objective trade-offs. The model is divided into two parts. First part is to use the evidence-based trust function and fuzzy logic model to integrate the group of detailed or imprecise evaluation data; this improves the reliability of the empirical data. Second, by aiming to maximize the overall design interest, SHVM in the coalitional game solves the optimal expectation for each objective and decides the optimal scheme. Finally, a shearer rocker height-adjusting device case study is presented to illustrate the applications, and a conceptual scheme trade-off decision prototype system is developed based on the approach for verification. This model is proven to be effective compared with the TOPSIS, VIKOR, and ELECTRE I.